PSYCHOLOGICAL WELL-BEING PADA WANITA PENDERITA KANKER PAYUDARA YANG TELAH MELAKUKAN MASTEKTOMI - Maria Devina; Brian Brian; Shanty Sudarji (Universitas Bunda Mulia, 2015)
The number of diseases in the world has many types and varieties, ranging from severe to mild. One of the diseases that are classified as severe and deadly cancer. Cancer is one of the diseases that are very scary for everyone, both in Indonesia and in the world, one of which is breast cancer. Breast cancer not only affects women, but can be attacked by men. In the world, breast cancer experienced by 99 % of women and 1 % of men. The aim of this study was to see how the image psychological well-being in middle age women with breast cancer who have a mastectomy. Psychological well-being itself has several aspects and factors that can be used in patients with breast cancer. The aspect is self-acceptance, positive relations with others, autonomy, environmental mastery purpose in life, and personal growth. As for the factors that are owned psychological well-being is of age, gender, socioeconomic status, education , and culture.Keywords: breast cancer, middle age, psychological well-being.